Said Nursi’s Thoughts on Environmental Sustainability in Risale-I Nur - Sempo, Muhammad Widus; Khosim, Norullisza (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
This study addresses the standpoint of Bediuzzaman Said Nursi about the importance of holistic Islamic view towards living sustainably. Nowadays, human beings are less aware of the environmental destruction that increasingly causing harm to all. The problem arises from people’s abandonment in manifesting the infinite meaning of Allah’s attributes (al-Asma’ al-Husna) in daily practice. In fact, Allah the Most Merciful has fulfilled all the needs of His creatures to the very least. However, we do not take into account the importance of implementing the meaning of al-Asma’ al-Husna to make any progress in all aspects of life. Therefore, Said Nursi was a leading Muslim scholar of the 20th century who strived to give greater understanding and explanation to the importance of manifestation of the God’s Divine Name for the people towards creating awareness of environmental sustainability. This article focuses on the values and ethics related to environmental sustainability from the Bediuzzaman Said Nursi’s perspective in Risale-i Nur. Therefore, the researchers have read the Risale-i Nur inductively to capture Said Nursi’s thought on environmental sustainability. In conclusion, the results of the study found that a good understanding towards (i) the purpose of Allah's creation, (ii) the meaning of al-Asma’ al-Husna and its manifestation, (iii) and the importance of ethics or behaviour towards creatures, can help maintain environmental sustainability and survival of biodiversity.